2020
DOI: 10.1186/s12885-020-07004-y
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of patient-tailored FOLFIRINOX as a first-line chemotherapy for patients with advanced biliary tract cancer

Abstract: Background: FOLFIRINOX is a pillar first-line regimen in the treatment of pancreatic cancer. Historically, biliary tract cancer (BTC) and pancreatic cancer have been treated similarly with gemcitabine alone or combined with a platinum compound. With growing evidence supporting the role of fluoropyrimidines in the treatment of BTC, we aimed at assessing the outcomes of patients (pts) with BTC on frontline FOLFIRINOX. Methods: We retrospectively analyzed data of all our consecutive patients with locally advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Previous studies showed that when compared with gemcitabine, FOLFIRINOX prolonged survival for patients with metastatic pancreatic cancer [ 9 , 17 ]. For advanced biliary tract cancer, a retrospective study showed median OS of patients with first-line FOLFIRINOX was as long as 15 months [ 11 ]. In addition, several studies have demonstrated the efficacy and safety of FOLFIRINOX or mFOLFOX as a second-line treatment for advanced CCA [ 12 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that when compared with gemcitabine, FOLFIRINOX prolonged survival for patients with metastatic pancreatic cancer [ 9 , 17 ]. For advanced biliary tract cancer, a retrospective study showed median OS of patients with first-line FOLFIRINOX was as long as 15 months [ 11 ]. In addition, several studies have demonstrated the efficacy and safety of FOLFIRINOX or mFOLFOX as a second-line treatment for advanced CCA [ 12 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As therapeutic similarities in sensitivity to fluorouracil, platinum and gemcitabine exist between CCA and pancreatic cancer [ 10 ], mFOLFIRINOX might show better efficacy than Gemox in treating patients with CCA. Ulusakarya et al [ 11 ] had reported that the median OS of patients with advanced biliary tract cancer treated with first-line FOLFIRINOX was as long as 15 months. Recently, Angela et al [ 12 ] reported mFOLFOX (folinic acid, fluorouracil, and oxaliplatin) improved the prognosis of patients with advanced biliary tract cancer after progression on cisplatin and gemcitabine.…”
Section: Introductionmentioning
confidence: 99%
“…This regimen is being evaluated against cisplatin and gemcitabine in the ongoing Phase III SWOG 1815 trial (NCT03768414). The use of 5-fluorouracil (5-FU)/leucovorin/irinotecan/oxaliplatin (FOLFIRINOX) as first-line treatment has led to a disease control rate (DCR) of 75% and OS of 15 months in small retrospective series [24,25].…”
Section: Conventional Chemotherapymentioning
confidence: 99%
“…After failure of GemCis, recent studies recommend the use of FOLFOX as second line treatment of ABTC [2,15]. In addition, various triple therapies [16] such as FOLFIRINOX [17][18][19] or irinotecan / fluorouracil / leucovorin [20], checkpoint inhibitors alone or in combination with chemotherapy [21], and molecular targeted therapies such as the inhibition of fibroblast growth factor receptor (FGFR) 1-4 [22][23][24][25][26] or isocitrate dehydrogenase (IDH) 1 [27] are currently being investigated in clinical trials (reviewed in [21,28]).…”
Section: Introductionmentioning
confidence: 99%